2015
DOI: 10.1016/j.ijsolstr.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of anisotropy and tension–compression asymmetry on the torsional response of AZ31 Mg

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…For the Zirconium and the AZ31-Mg alloy under study, the anisotropy parameters of the CPB06 yield criterion were previously identified in [6] and [16], respectively. In those studies, different sets of anisotropy parameters were identified for different levels of the plastic work.…”
Section: Parameters Identification For the Zirconium And Az31mg Alloymentioning
confidence: 98%
See 4 more Smart Citations
“…For the Zirconium and the AZ31-Mg alloy under study, the anisotropy parameters of the CPB06 yield criterion were previously identified in [6] and [16], respectively. In those studies, different sets of anisotropy parameters were identified for different levels of the plastic work.…”
Section: Parameters Identification For the Zirconium And Az31mg Alloymentioning
confidence: 98%
“…The CPB06 yield criterion is used in this section to describe the anisotropic behavior of two metallic materials, known for exhibiting strong tension-compression asymmetry: Zirconium [6] and the AZ31-Mg alloy [16]. These materials were selected since the anisotropy parameters for the CPB06 yield criterion were previously determined [6,16].…”
Section: Application To Zirconium and Az31-mg Alloymentioning
confidence: 99%
See 3 more Smart Citations